Art Auctions and the Poorer Rich: The Impact of the 2015 Stock Market Sell-off on the Emerging Philippine Art Market - Santiago, Joseph Sedfrey S (Archīum Ateneo, 2018)
This paper looks into the Philippine secondary art market, which has recently emerged with the country’s booming economy. Specifically, the paper aims to determine the effect of the August 2015 stock market sell-off on prices and profitability of art auction sales in the Philippines. Works of art may be considered as alternative investment goods for stocks. There may be greater demand for artworks as part of an investment diversification strategy when the equity market is bearish. On the other hand, artworks may also be part of a conspicuous consumption behavioral pattern, such that when income and wealth levels fall, the demand for artworks drops. To determine the net effect of stock market conditions on the Philippine art market, an empirical model is estimated using the ratio of the auctions’ hammer price to the starting bid as a measure of art market profitability and vitality. Our regression results reveal that artworks are more of a conspicuous consumption good in the Philippines. Reduced income and wealth after the stock market plunge in August 2015 led to lower willingness to pay for artworks and lower returns in the September 2015 auctions compared to the September 2014 auctions. The “poorer rich” effect appears to prevail over the alternative investment effect in the Philippines.